It's a wonderful life [videorecording (Blu-Ray)] - Capra, Frank, 1897-1991; Goodrich, Frances; Hackett, Albert; Stewart, James, 1908-1997; Reed, Donna, 1921-1986; Barrymore, Lionel, 1878-1954; Mitchell, Thomas, 1892-1962; Travers, Henry, 1874-1965 (Paramount, 2016)
George Bailey has so many problems he is thinking about ending it all and it's Christmas! As the angels discuss George, his life is shown in flashback. As George is about to jump from a bridge, he ends up rescuing his guardian angel, Clarence. Clarence then shows George what his town would have looked like if it hadn't been for all of his good deeds over the years. Will Clarence be able to convince George to return to his family and forget suicide?